2020
DOI: 10.33102/sainsinsani.vol5no2.178
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Women Participation in Sports: Critical Analysis of Presupposition Strategies in Arabic Online News Discourse

Abstract: Saudi women face many restrictions compared to other Arab or Muslim women as they have been barred (legally and or culturally) from doing many things by themselves or can only do some activities with the presence of a male guardian. Over the last two decades, there are many struggles recorded by the mass media, particularly the newspapers and the satellite channels. The media has been reported on the debates between groups demanding more rights for Saudi women and the conservative groups preserving the fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among the transformational leadership sub-scales, inspirational motivation was observed to be the most frequently displayed subscale. Given the various socio-cultural barriers for females in Saudi Arabia (23)(24)(25)(26)(27)(28) from entering sports, motivational approach could be an effective strategy to boost the morale and engagement of the female sports persons in Saudi Arabia. Accordingly, inspirational motivation exhibited strong correlation with sports engagement sub-scales including vigor, dedication, and absorption; compared to other transactional leadership sub-scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the transformational leadership sub-scales, inspirational motivation was observed to be the most frequently displayed subscale. Given the various socio-cultural barriers for females in Saudi Arabia (23)(24)(25)(26)(27)(28) from entering sports, motivational approach could be an effective strategy to boost the morale and engagement of the female sports persons in Saudi Arabia. Accordingly, inspirational motivation exhibited strong correlation with sports engagement sub-scales including vigor, dedication, and absorption; compared to other transactional leadership sub-scales.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is issues with gender equality in sports participation globally, its impact was mainly observed in the Middle East till the past decade (23). Furthermore, it was observed that when compared to other Arab or Muslim women, Saudi women are subject to a greater number of limitations since they are prohibited (legally or culturally) from doing many things by themselves and are required to have a male guardian present to participate in some activities (24). Young Arabic Muslim women who participate in sports are perceived as taking on a challenge to the limits of their ethnic identities when compared to their peers who do not (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most significant findings in these studies is that the newspaper readership received a substantial impact on institutionalised participation. Other studies are concerned about revealing that political institutions have used the media to serve their ideas, stands, and promote their ideology and propaganda (Harun, Ismail, Daoudi, & Thompson, 2018;Harun & Ismail, 2020;Ismail et al, 2018, Ismail, 2019Mellor, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…With the emergence of Arabic unity discourse and Arab national identity in the 1950s, further enhanced in the 1990s with Arab transnational television broadcasting, Arab media has been exploited to serve this political purpose (Lahlali, 2011). In addition, previous literature on the Arab media has highlighted the features of Arabic transnational media outlets by focusing on bias and independence of various media institutions (Harun, Ismail, Daoudi, & Thompson, 2018;Harun & Ismail, 2020;Ismail et al, 2018;Ismail, 2019;Mellor, 2011;Miladi, 2006;Zayani & Ayish, 2006). Despite the claim of impartial, independence, objectivity, and privately-owned, these Arabic media outlets have been used as political tools and controlled by people close to the government (Ismail et al, 2018;Ismail, 2019;Harun, Ismail, Daoudi, & Thompson, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%